The inhabited territory. Parkour, motor skills and affections in the city of Quito: parkour, motor skills and affections in the city of Quito - Vásconez Vaca, Dennis Javier (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article is a reflection on corporal movement and affectivities in the city of Quito, through a deep observation and a long reflection on these issues from the perspective of parkour, a motor practice dedicated to transit urban spaces in the most fluid and effective way possible, using only the body. Through the experience of learning and practice of parkour, among the activities of the Étre Fort collective, this study explores the transformations that the exercise of this discipline entails on the city, its spatial production and its inhabited territory, at the same time that reflects on the affective elements that arise in this practice, and their role in these transformations.